Study at Non-formal Education Institution PKBM: The Suitability between IT and Business Strategy Using SAMM - Lestari Retnawati; Nia Saurina; Firman Pratama; Udik Pudjianto (STAI Hubbulwathan Duri, 2024)
Community Learning Activity Centers (PKBM) provide non-formal education to enhance skills and education access, particularly for individuals excluded from formal systems. PKBM Cerme Gresik integrates information technology (IT) to improve operations; however, aligning IT with business strategies remains a challenge critical for optimizing performance. This study evaluates the alignment between IT and business strategies at PKBM Cerme Gresik using the Strategic Alignment Maturity Model (SAMM). A quantitative approach, involving surveys, was employed to assess six SAMM dimensions: Communication, Competence Value Measurement, Governance, Partnership, Scope Architecture, and Skills. Scores were aligned with SAMM's five maturity levels (1–5). The SAMM evaluation revealed the following scores: Communication (3.0), Competence Value Measurement (2.1), Governance (1.6), Partnership (2.5), Scope Architecture (2.25), and Skills (2.16). Communication was rated at level 3 (established process), while other dimensions fell at level 2 (committed process), except Governance, which was at level 1 (initial process). The overall alignment maturity score was 2, indicating a committed process. PKBM Cerme Gresik demonstrates a partial commitment to IT-business alignment, focusing on operational coordination. However, challenges such as limited resources, inefficient IT management, and insufficient alignment hinder progress toward higher maturity levels. The study concludes that IT-business strategy alignment at PKBM Cerme Gresik is at a committed process level (level 2). To advance educational impact, efforts to enhance IT resources, management efficiency, and alignment must be prioritized.